The letters of Psellos - Jeffreys, Michael J.,Lauxtermann, Marc D. (Oxford University Press, 2017)
The Letters of Psellos' is the first detailed study of the correspondence of Michael Psellos, a leading Byzantine intellectual, politician, and writer of the eleventh century. Psellos' corpus of over 500 letters represents a historical source of great significance for the study of society and culture of the time: literary masterpieces in and of themselves, yet often complex and difficult to understand in their entirety, they not only rebound with subtlety and humour, but also offer invaluable information on myriad subjects ranging from the political culture of Byzantium and its civil administration to social codes, religious beliefs, and popular culture.–Provided by the publisher Introduction / Marc D. Lauxtermann – Educational networks in the letters of Michael Psellos / Floris Bernard – Michael Psellos and the monastery / Michael Jeffreys – Constantine, nephew of the patriarch Keroularios, and his good friend Michael Psellos / Michael Jeffreys – The intertwined lives of Michael Psellos and John Mauropous / Marc D. Lauxtermann – Venomous praise : some remarks onMichael Psellos' letters to Leon Paraspondylos / Diether Roderich Reinsch – Summaries of the letters of Michael Psellos / Michael Jeffreys
Keywords: Psellus; Michael; Correspondence